2017
DOI: 10.2527/jas2017.1464
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tannic acid on growth performance, carcass characteristics, digestibility, nitrogen volatilization, and meat lipid oxidation of steers fed steam-flaked corn–based finishing diets

Abstract: Effects of a tannic acid blend (ByPro; Silvateam USA, Ontario, CA) added to steam-flaked corn-based fishing diets on beef cattle growth performance, carcass characteristics, nutrient digestibility, fecal N volatilization, and meat lipid oxidation were evaluated. Steers ( = 144; 349 ± 25 kg initial BW) were blocked by initial BW and assigned randomly to 1 of 3 treatments with 12 pens/treatment and 4 steers/pen and fed ad libitum. Treatments included a control (CON; no ByPro) and ByPro fed at 30 or 60 g DM/steer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…As a result, the formation of MbO 2 (ferroheme combined with oxygen) is responsible for the consumer-desired bright cherry-red lean color (Mancini and Hunt, 2005;Tabke et al, 2017). Consumers usually discriminate against the presence of brown or discolored lean meat, a result of oxidation of MbO 2 to MMb (caused by Fe 2+ in heme oxidizing to Fe 3+ ) (Bekhit and Faustman, 2005;Tabke et al, 2017). In general, when the flesh is observed to be dark brown with the naked eye, more than 60% of Mb has converted to MMb.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the formation of MbO 2 (ferroheme combined with oxygen) is responsible for the consumer-desired bright cherry-red lean color (Mancini and Hunt, 2005;Tabke et al, 2017). Consumers usually discriminate against the presence of brown or discolored lean meat, a result of oxidation of MbO 2 to MMb (caused by Fe 2+ in heme oxidizing to Fe 3+ ) (Bekhit and Faustman, 2005;Tabke et al, 2017). In general, when the flesh is observed to be dark brown with the naked eye, more than 60% of Mb has converted to MMb.…”
Section: Discussionmentioning
confidence: 99%
“…In a 226-d study, Barajas et al (2011) observed a 6% increase on DMI in bull (initial weight = 184 kg) fed a growing-finishing diet supplemented with 0.34% of a blend of condensed and hydrolyzable tannins. Likewise, in a 140-d trial, Tabke (2014) observed a linear in DMI of feedlot bulls fed a finishing diets supplemented with 0%, 0.3%, or 0.6% of blend of condensed and hydroyzable tannin. Similar responses in DMI to tannin supplementation of higher forage diets have been also reported in feeding trials involving goats (Puchala et al 2005), lambs (Douglas et al 1995), and in cows (Woodward et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, total ADG and BW were not affected, although we observed a higher ADG at the end of the trial. Tabke et al [49] supplemented tannic acid (HT) into steam-flaked corn-based finishing diets of steers. Overall, no effects were observed for ADG, carcass characteristics, hot carcass weight, longissimus muscle area, fat thickness, and yield grade during the study in any treatment.…”
Section: Effects Of Tannins On Growth Performance Of Bullsmentioning
confidence: 99%